Biopolymer nanocomposites : processing, properties, and applications - Dufresne, Alain, 1962-; Thomas, Sabu; Pothan, Laly A. (Wiley, 2013)
"The book is an attempt to introduce various biopolymers and bionanocomposites to a student of material sciences. Going beyond mere introduction, the book delves deep into the characteristics of various biopolymers and bionanocomposites and discuses, the nuances of their preparation with a view to help researchers to find out newer and novel applications. Chapter 2 of the book, for instance, describes the preparation of Chitin Nanofibers and their Composites and goes even to the basics like isolation of CNFs from different sources. Chapter 3 is on Chemical Modification of Chitosan and its Biomedical Application. While, Biometric lessons for processing chitin based composites are provided in Chapter 4, the next chapter deals with Morphological and Thermal Investigations of Chitin-based Nanocomposites. Mechanical properties of chitin-based nanocomposites are discussed in Chapter 6 and Preparation and Applications of Chitin Nanofibers/Nanowhiskers is the topic of Chapter 7. Thus, Chapters 2 to 7 are allotted to Chitin and related topics"--Vydavatelská anotace
Keywords: nanokompozitní materiály; biopolymery; nanocomposites; biopolymers; kolektivní monografie; collective monographs